2018
DOI: 10.1016/j.str.2018.02.017
|View full text |Cite
|
Sign up to set email alerts
|

An Intracellular Allosteric Modulator Binding Pocket in SK2 Ion Channels Is Shared by Multiple Chemotypes

Abstract: Small conductance potassium (SK) ion channels define neuronal firing rates by conducting the after-hyperpolarization current. They are key targets in developing therapies where neuronal firing rates are dysfunctional, such as in epilepsy, Parkinson's, and amyotrophic lateral sclerosis (ALS). Here, we characterize a binding pocket situated at the intracellular interface of SK2 and calmodulin, which we show to be shared by multiple small-molecule chemotypes. Crystallization of this complex revealed that riluzole… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
38
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(44 citation statements)
references
References 27 publications
6
38
0
Order By: Relevance
“…We first constructed the human SK2/calmodulin model (PSK2) using SWISS-MODEL server and docked the ligands Riluzole and CyPPA analog 1 (PDB ligand ID: 658, see section 2.1), onto the predicted binding site. The predicted site is consistent with the reported results (Cho et al, 2018). Then the residues V481 and A477 in the binding pocket were virtually mutated and the mutation effects were assessed via binding energies (MM-GBSA G Bind ) calculation.…”
Section: Introductionsupporting
confidence: 82%
See 2 more Smart Citations
“…We first constructed the human SK2/calmodulin model (PSK2) using SWISS-MODEL server and docked the ligands Riluzole and CyPPA analog 1 (PDB ligand ID: 658, see section 2.1), onto the predicted binding site. The predicted site is consistent with the reported results (Cho et al, 2018). Then the residues V481 and A477 in the binding pocket were virtually mutated and the mutation effects were assessed via binding energies (MM-GBSA G Bind ) calculation.…”
Section: Introductionsupporting
confidence: 82%
“…It was also reported that ligands of two different chemical classes, Riluzole and its analog NS309, and CyPPA and its analogs, all bind to the same binding site where the interface of SK2 and calmodulin is. In addition, two key residues in the binding site were mutated to investigate how different mutations affect the potency of two ligands (Cho et al, 2018). As a proof of concept, we chose SK2 as the target to examine the protocol we proposed.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…It does not activate Ca 2+ and other voltage-dependent K + currents; however, it causes an inhibition of BK and Na + currents (12). CyPPA binds to and allosterically modulates via a binding pocket situated at the intracellular interface of SK and calmodulin, which increases the SK/calmodulin's affinity for Ca 2+ (19). Due to overlapping activation ranges between SK3 (EC 50 = 5.6 ± 1.6 μmol/l) and SK2 (EC 50 = 14 ± 4 μmol/l) and the possibility of forming heteromeric complexes (20,21), whether CyPPA at the current concentration can activate heteromeric channels remains unclear.…”
Section: Discussionmentioning
confidence: 99%
“…injections with CHZ converted bursting PCs to tonic spike generation state in aging SCA2-58Q animals (Egorova et al, 2016). Another chemical compound riluzole attracts and allosterically activates the SK2 channel molecules (Cho et al, 2018). A randomized, double-blind, placebo-controlled trial on a mixed population of ataxia patients with different forms of hereditary cerebellar ataxia demonstrated that the exposure to 100 mg/day riluzole alleviated the SARA scores in patients and did not reveal any life-threatening toxicity (Romano et al, 2015).…”
Section: Chz As a Potential Treatment Of Ataxic Symptoms In Hdmentioning
confidence: 99%